IMPORTANCE OF MICROCALCIFICATIONS IN MAMMOGRAPHIC DIFFERENTIATION OF THE INVASIVE DUCTAL BREAST CANCER AND OF THE DUCTAL CARCINOMA IN SITU - Šarac, Vanja; Nadrljanski, Mirjan (Medicinski podmladak, 2017)
Abstract Introduction: Microcalcifications represent a significan tand reliable sign of the presence of the malignant breast lesion. Aim: The aim of the paper is to radiologically evaluate the type and distribution of suspicious microcalcifications in patients with invasive ductal carcinoma (IDC) and ductal carcinoma in situ (DCIS). Material and Methods: Retrospective analysis includes the evaluation of the type and distribution of suspicious microcalcifications in patients with histologically verified malignant lesions: invasive ductal carcinoma (N1=40 pts.) and ductal carcinoma in situ (N2=40 pts.). Standardised mediolateral oblique and cranicaudal views were selected for the evaluation of the images taken onthe full-field digital mammograph (FFDM «Selenia», Institute of Oncology and Radiology of Serbia, Belgrade), on the dedicated workstation of the mammography unit, with the aid of the software for lesion evaluation. Results: Eight patients with invasive ductal carcinoma (20%) had no suspicious microcalcifications, as opposed to the patients with ductal in situ carcinoma where all patients had suspicious microcalcifications (p<0.05). In the subgroup of patients with invasive ductal carcinoma, the most frequent type of microcalcifications included the fine pleomorphic calcifications (75%). In patients with ductal carcinoma in situ, amorphous (57.5%) and linear / branching microcalcifications were more frequent than other types (55%). Conclusion: The results of this study show that the amorphous microcalcifications segmental distribution usually detected in the subgroup with DCIS, which coincides with published results. With acceptable sensitivity and specificity, amorphous microcalcifications and linear distribution segment represents a specific mammographic findings in the detection of DCIS. Keywords: microcalcifications, invasive ductal carcinoma, ductal carcinoma in situ, mammography